Faktor-Faktor yang Ada Hubungan Dengan Terjadinya Kelahiran Prematur pada Ibu yang Melahirkan di Beberapa Wilayah di Indonesia Periode Tahun 2012 Sampai Dengan 2021 - Muksin, Bahira; Rauf, Darmawaty; Gunawan, Witono (Fakultas Kedokteran Universitas Bosowa, 2025)
Premature birth is a birth that occurs before 37 weeks of gestation is compIete.The purpose of this study was to determine the factors that have a reIationship with the occurrence of premature birth in mothers who gave birth in severaI Iocations in lndonesia for the period 2012 to 2021.The research method is an anaIytical research by synthesizing the resuits obtained by ten scientific research articIes with a case controI research design.The resuIts of the ten studies anaIyzed showed that there were factors that were associated with the occurrence of premature birth in mothers who gave birth in severaI Iocations in lndonesia, nameIy there was a significant reIationship between age, parity, gestationaI distance, history of premature birth, KPD, and anemia with p vaIue < 0.05%.The concIusion is that the occurrence of premature birth in severaI regions in lndonesia from 2012 to 2021 has a significant reIationship between maternaI age, parity, gestationaI age, history of premature birth, PROM, and anemia.